Modified mesoporous alumina, hydrogenation catalyst and preparation and use thereof
Patent Information
- Application Number
- CN202510570103.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
当前,普通氧化铝酸性较为单一、负载金属时与活性组分间的作用太强,导致深度加氢的目的还不能很好的实现
[0045]本发明提供了一种改性介孔氧化铝,其中,改性元素为钛,所述改性介孔氧化铝中,中强酸量占总酸酸量的59%~65%。本发明改性介孔氧化铝中钛、铝两种金属相互作用,可以进一步优化介孔氧化铝的孔结构以及表面酸性。
Smart Images

Figure BDA0005386945950000111 
Figure BDA0005386945950000112 
Figure BDA0005386945950000121
Abstract
Description
Technical Field
[0001] This invention relates to a mesoporous material, belonging to the field of catalyst preparation, specifically to a modified mesoporous alumina, a hydrogenation catalyst, and their preparation and application. Background Technology
[0002] With the increasing trend of heavier and lower-quality crude oil worldwide, heavy oil hydrotreating technology plays an increasingly important role in the efficient utilization and lightening of crude oil. Alumina, as the main carrier of hydrotreating catalysts, possesses characteristics such as a large specific surface area, excellent pore structure, a certain acid strength distribution, and high hydrothermal and thermal stability, playing a crucial role in the hydrotreating process. Currently, ordinary alumina has relatively simple acidity, and the interaction between loaded metals and active components is too strong, preventing the full realization of deep hydrotreating goals. Especially in the hydrotreating of heavy oil, the small pore size of ordinary alumina restricts the diffusion of large molecules during the reaction, making the catalyst more prone to deactivation, and the utilization rate of active metals needs further improvement.
[0003] CN104923215A discloses an ordered mesoporous alumina material supported on noble metals, its synthesis method, and its application. The method includes the following steps: mixing an acid, an alcohol, and a nonionic surfactant uniformly; adding a hydrophobic noble metal salt and an aluminum salt; mixing uniformly to obtain a mixed solution; maintaining the mixed solution at 30–60°C for a period of time to evaporate the solvent; and then calcining at 300–600°C to obtain the ordered mesoporous alumina material supported on noble metals. This ordered mesoporous alumina material supported on noble metals can be used to prepare catalysts for the oxidation of carbon monoxide.
[0004] Currently, there are many ways to synthesize alumina, but how to prepare alumina-based support materials with better overall performance, and on the basis of the above, prepare hydrogenation catalysts with excellent hydrogenation and demetallization performance, is an important research direction. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a modified mesoporous alumina, a hydrogenation catalyst, and its preparation and application. The hydrogenation catalyst prepared using the modified mesoporous alumina of this invention as the support component exhibits strong hydrogenation activity in hydrogenation demetallization reactions, significantly improving its reaction performance and ensuring long-term stable operation of the hydrogenation unit.
[0006] The first aspect of the present invention provides a modified mesoporous alumina, wherein the modifying element used in the modified mesoporous alumina is titanium, and the amount of medium-strong acid in the modified mesoporous alumina accounts for more than 60% of the total acid content, preferably 62.5% to 65.5%.
[0007] Furthermore, the modified mesoporous alumina has a specific surface area of 300–500 m². 2 / g, preferably 320-380m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–20.0 nm, and a pore volume of 1.10–1.50 mL / g, preferably 1.26–1.40 mL / g.
[0008] Furthermore, in the modified mesoporous alumina, the molar ratio of titanium to aluminum is 0.2 to 0.8.
[0009] Furthermore, in the modified mesoporous alumina, the amount of medium-strong acid accounts for 59% to 65% of the total acid content, preferably 62% to 65%. The total acid content refers to the sum of the amounts of weak acid, medium-strong acid, and strong acid. The total acid content is 0.215 to 0.275 mmol / g, preferably 0.215 to 0.240 mmol / g.
[0010] A second aspect of the present invention provides a method for preparing the above-mentioned modified mesoporous alumina, comprising the following steps:
[0011] (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A;
[0012] (2) Mix the template agent and alcohol to obtain solution B;
[0013] (3) Mix solution A, solution B and the solution containing titanium source to obtain solution D;
[0014] (4) Add a bifunctional structure directing agent to solution D, perform hydrothermal treatment, dry, and calcine to obtain modified mesoporous alumina.
[0015] Further, in step (1), the pre-hydrolysis is carried out under stirring conditions, and the stirring rate is not particularly limited. The temperature of the pre-hydrolysis is 20-60℃, and the pre-hydrolysis time is 1-12 hours. Further, the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide. The acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid. The alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol.
[0016] Further, in step (1), the alcohol / aluminum molar ratio is 10.0 to 80.0, preferably 15.0 to 50.0.
[0017] Further, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 2.0 to 6.0.
[0018] Further, preferably, in step (1), the aluminum source, acid, and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution, and then an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. The amount of the ionic emulsifier added is related to the amount of the precursor solution by 5–15 g / 100 mL.
[0019] Furthermore, the ionic emulsifier is one or more of anionic emulsifiers such as sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt (chemical structure formula RO(CH2CH2O)n-SO3Na (n=1~15, R is a fatty alkyl group of C10~C22)).
[0020] Furthermore, the molar ratio of the sum of the aluminum source in step (1) and the titanium source in step (3) to the molar ratio of the template agent in step (2) is 50 to 90.
[0021] Further, in step (2), the template agent is at least one of P123, SDBS, and AOT, preferably P123. Mixing is carried out under stirring conditions, with no particular limitation on the stirring rate. The stirring temperature is 30–60°C, and the stirring time is 1–4 h. In step (2), the molar ratio of alcohol to template agent is 300–1000.
[0022] Further, in step (3), the titanium source-containing solution comprises a titanium source, an acid, and an alcohol, wherein the alcohol is preferably ethanol, and the acid is preferably nitric acid; the titanium source is selected from at least one of titanium isopropoxide, tetrabutyl titanate, methyl titanate, and tetraethyl titanate. In the titanium source-containing solution, the volume ratio of alcohol to acid is 4–12. Further, the titanium source, alcohol, and acid are mixed to obtain a titanium source-containing solution, denoted as solution T. Preferably, in the titanium source-containing solution, the ratio of the mass of titanium element to the sum of the volumes of acid and alcohol is 0.02–0.15 g / mL, more preferably 0.05–0.11 g / mL.
[0023] Further, preferably, in step (3), solution A is first added dropwise to solution B to obtain solution C, and then solution T is added dropwise to solution C to obtain solution D. Preferably, the molar ratio of the titanium source to the aluminum source in step (1) is 0.2 to 0.8.
[0024] Furthermore, in step (3), the mixing is carried out under stirring conditions, and there is no particular limitation on the stirring rate. The stirring temperature is 30-60℃, and the stirring time is 1-4h.
[0025] Further, in step (4), the bifunctional structure directing agent is polyethylene glycol-distearate phosphatidylethanolamine (molecular weight 500-5000). Further, the molar ratio of the bifunctional structure directing agent to the sum of the bifunctional structure directing agent and the aluminum source in solution A is 0.05-0.25.
[0026] Further, in step (4), the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 165-245℃, and time 3-12h, preferably 4-8h.
[0027] Further, in step (4), after the hydrothermal treatment, the alumina is first cooled to 25°C, then dried and calcined to obtain mesoporous alumina. The drying temperature is 120–200°C, and the drying time is 4–10 hours. The calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
[0028] A third aspect of the present invention provides a hydrogenation catalyst, the hydrogenation catalyst comprising a composite support containing a first active metal and a second active metal, wherein the composite support containing the first active metal comprises the modified mesoporous alumina, activated carbon and the first active metal described in the first aspect.
[0029] Furthermore, the first active metal is selected from at least one of Group VIB metals, preferably molybdenum; the second active metal is selected from at least one of Group VIII metals, preferably nickel.
[0030] Furthermore, in the composite carrier containing the first active metal, the mass ratio of modified mesoporous alumina to activated carbon is 2.5 to 6.0.
[0031] Furthermore, in the catalyst, based on the mass of the catalyst, the content of Group VIB metal oxides is 8.0% to 18.0%, preferably 10.0% to 15.0%, and the content of Group VIII metal oxides is 0.5% to 10%, preferably 1.0% to 6.0%.
[0032] Furthermore, in the catalyst, the mesopore volume with a pore size of 6.0–25.0 nm accounts for 20.0%–48.0% of the total pore volume, preferably 41.5%–48.0%, and the macropore volume with a pore size of 50.0–300.0 nm accounts for 20.0%–35.0% of the total pore volume, preferably 24.5%–35.0%.
[0033] Further, in the hydrogenation catalyst, the molar ratio of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and Lewis acid is 0.310–0.390, preferably 0.350–0.388. In the catalyst, the amount of Brønsted acid is 11.0–17.9 μmol / g, preferably 15.4–17.7 μmol / g.
[0034] The fourth aspect of this invention provides a method for preparing the above-mentioned catalyst, comprising the following steps:
[0035] (I) Modified mesoporous alumina, activated carbon, first active metal source and molding aid are mixed and shaped, dried and calcined to obtain a composite carrier modified with the first active metal.
[0036] (II) The second active metal is loaded onto the composite support obtained in step (I), dried, and calcined to obtain the catalyst.
[0037] Further, in step (I), the activated carbon is a high-temperature activated carbon, with a minimum heat resistance temperature of not less than 700℃, preferably 700-800℃. The activated carbon has a pore volume of 1.0-1.8 mL / g, and the pore volume of pores with a diameter of 50.0-300.0 nm accounts for 15%-40% of the total pore volume.
[0038] Further, in step (I), the molding aid is one or more of guar gum powder, methylcellulose, etc. The molding method can be at least one of extrusion, tableting, and ball forming. The shaped product can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0039] Further, in step (I), the molding aid is added at a content of 1.0% to 8.0% of the total mass of modified mesoporous alumina and activated carbon.
[0040] Further, in step (I), the first active metal is one or more of VIBs, preferably molybdenum; further, the molybdenum source is selected from at least one of ammonium heptamolybdate and ammonium tetramolybdate. The mass of the first active metal, calculated as oxide, is 10% to 20% of the total mass of mesoporous alumina and activated carbon.
[0041] Further, in step (I), the drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0042] Further, in step (II), the preferred loading method is saturated impregnation. After impregnation, the catalyst is obtained through conventional filtration, washing, drying, and calcination. The drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0043] The fifth aspect of the present invention provides the application of the above-mentioned catalyst in the hydrodemetallization of residue oil.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] This invention provides a modified mesoporous alumina, wherein the modifying element is titanium, and the modified mesoporous alumina contains 59% to 65% medium-strong acid. The interaction between titanium and aluminum in the modified mesoporous alumina of this invention can further optimize the pore structure and surface acidity of the mesoporous alumina.
[0046] This invention provides a method for preparing modified mesoporous alumina. First, a self-assembly method is adopted, mainly by controlling the alcohol / aluminum molar ratio, the alcohol / template agent molar ratio, and the introduction method of the template agent. At the same time, titanium metal and a bifunctional structure directing agent are introduced during the self-assembly process. Combined with hydrothermal treatment, the specific surface area, pore structure, and surface acid distribution of the mesoporous alumina are further optimized.
[0047] Based on the above-mentioned modified mesoporous alumina material, it is mixed with high-temperature activated carbon with macropores and a main active metal (Group VIB metal) to form a catalyst. Finally, a co-active metal (Group VIII metal) is impregnated and loaded. Through the comprehensive coordination of each step, the resulting catalyst is used in the hydrodemetallization reaction of residue oil, which further significantly improves the stability of the catalyst. Detailed Implementation
[0048] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0049] In this invention, the specific surface area and pore volume of the samples were characterized using a Micromeritics ASAP2420 fully automated specific surface area analyzer from Micromeritics, Inc., USA. The treated samples were loaded into the fully automated specific surface area analyzer for property testing using a low-temperature nitrogen isothermal adsorption method. The specific surface area of the samples was calculated using the BET method.
[0050] In this invention, the determination of L-acid or Brønsted acid is performed using infrared spectroscopy. The instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 (USA). The determination method is as follows: The sample to be measured is ground and pressed into a thin sheet with a thickness of approximately 0.1 mm, which is then placed in an infrared cell. The in-situ infrared cell is heated from room temperature to 350 °C over a programmed temperature range of 20 min and held for 120 min, then cooled to 200 °C over a 10 min period. The in-situ cell is then evacuated to a vacuum of 0.01 Pa. The sample is scanned as the background spectrum, and pyridine vapor is used as a probe molecule to scan the sample at 200 °C. The total amount of total acid, Brønsted acid, and L-acid can then be obtained. The units for the amounts of Brønsted acid and L-acid are μmol / g.
[0051] In this invention, the acid content of moderately strong acids was determined using the NH3-TPD method. The instrument used was an Auto-ChemII 2920 chemisorption analyzer from Micron Instruments. Ammonia was used as the adsorption / desorption medium, and helium as the carrier gas. Programmed temperature desorption and chromatographic analysis were employed to obtain the acid content in different desorption temperature ranges. The acid content of weak acids corresponds to an ammonia desorption temperature below 200℃, the acid content of moderately strong acids corresponds to an ammonia desorption temperature of 200℃–400℃, and the acid content of strong acids corresponds to an ammonia desorption temperature above 400℃. The unit of acid content is mmol / g, which represents the amount of ammonia adsorbed per gram of molecular sieve. The sum of the acid content of weak, moderately strong, and strong acids is the total acid content.
[0052] In various embodiments of the present invention, the molecular weight of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine is 872.14.
[0053] Example 1
[0054] Preparation of modified mesoporous alumina in this example:
[0055] (1) Add 80g of aluminum isopropoxide and 50mL of nitric acid to 360mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 45g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0056] (2) Add 40g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0057] (3) Add solution A dropwise to B to obtain solution C; weigh 8g of titanium isopropoxide and dissolve it in 40mL of ethanol and 10mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0058] (4) Add 35g of bifunctional structure directing agent polyethylene glycol-distearate phosphatidylethanolamine to solution D and perform hydrothermal treatment at 165℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0059] Preparation of the catalyst in this example:
[0060] (I) 300g of the modified mesoporous alumina obtained above, 100g of high-temperature activated carbon (heat resistance temperature of 750℃, pore volume of 1.4mL / g, and pore volume of 50~300nm accounting for 30% of the total pore volume), 6g of guar gum powder, 84g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0061] (II) Take 57g of nickel nitrate and 540g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0062] Example 2
[0063] Preparation of modified mesoporous alumina in this example:
[0064] (1) Add 96g of aluminum isopropoxide and 84mL of nitric acid to 665mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 68g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0065] (2) Add 38g of template agent P123 to 290mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0066] (3) Add solution A dropwise to B to obtain solution C; weigh 10g of titanium isopropoxide and dissolve it in 105mL of ethanol and 18mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0067] (4) Add 46g of the bifunctional structure directing agent polyethylene glycol-distearate phosphatidylethanolamine to solution D and perform hydrothermal treatment at 170℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0068] Preparation of the catalyst in this example:
[0069] (I) 280g of the modified mesoporous alumina obtained above, 75g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.5mL / g, and pore volume of 50-300nm accounting for 35% of the total pore volume), 8g of guar gum powder, 74g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0070] (II) Take 52g of nickel nitrate and 465g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0071] Example 3
[0072] Preparation of modified mesoporous alumina in this example:
[0073] (1) Add 62g of aluminum isopropoxide and 42mL of nitric acid to 460mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 54g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0074] (2) Add 28g of template agent P123 to 240mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0075] (3) Add solution A dropwise to B to obtain solution C; weigh 11g of titanium isopropoxide and dissolve it in 89mL of ethanol and 15mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0076] (4) Add 42g of the bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine to solution D and perform hydrothermal treatment at 180℃ for 4h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0077] Preparation of the catalyst in this example:
[0078] (I) The modified mesoporous alumina obtained above, 340g, high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.5mL / g, and pore volume of 50-300nm accounting for 30% of the total pore volume), 10g of guar gum powder, 89g of ammonium heptamolybdate, and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0079] (II) Take 62g of nickel nitrate and 563g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0080] Example 4
[0081] Preparation of modified mesoporous alumina in this example:
[0082] (1) Add 51g of aluminum isopropoxide and 52mL of nitric acid to 420mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 55g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0083] (2) Add 28g of template agent P123 to 220mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0084] (3) Add solution A dropwise to B to obtain solution C; weigh 15g of titanium isopropoxide and dissolve it in 96mL of ethanol and 20mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0085] (4) Add 35g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine to solution D and perform hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0086] Preparation of the catalyst in this example:
[0087] (I) 290g of the modified mesoporous alumina obtained above, 80g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.3mL / g, and pore volume of 50-300nm accounting for 35% of the total pore volume), 6g of guar gum powder, 78g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0088] (II) Take 54g of nickel nitrate and 485g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0089] Example 5
[0090] Preparation of modified mesoporous alumina in this example:
[0091] (1) Add 52g of aluminum isopropoxide and 65mL of nitric acid to 520mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 62g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0092] (2) Add 25g of template agent P123 to 241mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0093] (3) Add solution A dropwise to B to obtain solution C; weigh 9g of titanium isopropoxide and dissolve it in 107mL of ethanol and 30mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0094] (4) Add 42g of the bifunctional structure directing agent polyethylene glycol-distearate phosphatidylethanolamine to solution D and perform hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0095] Preparation of the catalyst in this example:
[0096] (I) 320g of the modified mesoporous alumina obtained above, 90g of high-temperature activated carbon (heat resistance temperature of 700℃, pore volume of 1.4mL / g, and pore volume of 50~300nm accounting for 36% of the total pore volume), 8g of guar gum powder, 87g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0097] (II) Take 60g of nickel nitrate and 537g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0098] Example 6
[0099] Preparation of modified mesoporous alumina in this example:
[0100] (1) Add 80g aluminum isopropoxide and 50mL nitric acid to 360mL ethanol, stir at 25℃ for 4h to perform pre-hydrolysis, and obtain solution A;
[0101] (2) Add 40g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0102] (3) Add solution A dropwise to B to obtain solution C; weigh 8g of titanium isopropoxide and dissolve it in 40mL of ethanol and 10mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0103] (4) Add 35g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine to solution D and perform hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0104] The catalyst in this example was prepared according to the method described in Example 1.
[0105] Comparative Example 1
[0106] In this example, mesoporous alumina was prepared according to the method described in the literature ("Preparation and Properties of Templated Mesoporous Alumina Materials." Journal of Dalian Railway Institute 27.1 (2006): 71-75).
[0107] Weigh 80g of aluminum isopropoxide and dissolve it in 360mL of deionized water. Add 50mL of nitric acid to form a sol. Stir the solution in an 80℃ water bath for 1 hour. When the solution cools to 25℃, weigh 40g of P123 and dissolve it in the solution. Stir for 1 hour. Then, transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction. The filling degree is 70%, the hydrothermal reaction temperature is 100℃, and the reaction time is 24 hours. After the hydrothermal reaction is completed, let the autoclave cool to 25℃ and dry the reaction product in an oven at 60℃. Then, calcine it in a muffle furnace at 550℃ for 3 hours to obtain mesoporous alumina.
[0108] The catalyst in this example was prepared according to the method in Example 1.
[0109] Comparative Example 2
[0110] The modified mesoporous alumina in this example is the same as in Example 1.
[0111] Preparation of the catalyst in this example:
[0112] (I) The above-obtained modified mesoporous alumina 400g, guar gum powder 6g, ammonium heptamolybdate 84g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier.
[0113] (II) Take 57g of nickel nitrate and 540g of deionized water to prepare a second active metal impregnation solution containing metallic nickel. Saturate the composite support obtained in step (I) with the second active metal impregnation solution. After drying at 120℃ for 6h and calcining at 550℃ for 4h, the catalyst is obtained.
[0114] Comparative Example 3
[0115] This example of mesoporous alumina is the same as in Example 1.
[0116] In this example, no active metal molybdenum is introduced in step (I) of the catalyst preparation process. The mass of MoO3 introduced into the catalyst by the molybdenum-nickel impregnation solution in step (2) is 100% of the total MoO3 loading in the catalyst.
[0117] (I) 300g of the modified mesoporous alumina obtained above, 100g of high-temperature activated carbon (heat resistance temperature of 750℃, pore volume of 1.4mL / g, and pore volume of 50~300nm accounting for 30% of the total pore volume), 6g of guar gum powder and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0118] (II) Prepare a nickel-molybdenum impregnation solution by taking nickel nitrate, ammonium heptamolybdate and deionized water, and then saturate the composite support obtained in step (I) with it. After drying at 120°C for 6 hours and calcining at 550°C for 4 hours, the catalyst is obtained.
[0119] Comparative Example 4
[0120] Preparation of mesoporous alumina in this example:
[0121] (1) Add 80g of aluminum isopropoxide and 50mL of nitric acid to 215mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 45g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0122] (2) Add 40g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0123] (3) Add solution A dropwise to B to obtain solution C; weigh 8g of titanium isopropoxide and dissolve it in 40mL of ethanol and 10mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0124] (4) Add 35g of bifunctional structure directing agent polyethylene glycol-distearate phosphatidylethanolamine to solution D and perform hydrothermal treatment at 165℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0125] The catalyst in this example was prepared according to the method in Example 1.
[0126] Comparative Example 5
[0127] Preparation of mesoporous alumina in this example:
[0128] (a) 64 g of aluminum isopropoxide and 45 mL of nitric acid were added to 350 mL of ethanol and stirred at 25 °C for 4 h to perform pre-hydrolysis and obtain a precursor solution; 48 g of sodium dodecyl sulfate was added to the precursor solution and stirred for another 3 h to obtain solution A.
[0129] (b) Add 36g of template agent P123 to 420mL of ethanol, stir at 25°C for 6h to obtain solution B;
[0130] (c) Add solution A obtained in step (a) dropwise to solution B to obtain solution C. Stir solution C at 50°C for 4 hours, dry it in an oven at 180°C for 4 hours, and then calcine it in a muffle furnace at 550°C for 3 hours to obtain mesoporous alumina.
[0131] Comparative Example 6
[0132] Preparation of modified mesoporous alumina in this example:
[0133] (1) Add 80g of aluminum isopropoxide and 50mL of nitric acid to 360mL of ethanol and stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 45g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0134] (2) Add 40g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0135] (3) Add solution A dropwise to B to obtain solution C; weigh 5g of titanium isopropoxide and dissolve it in 40mL of ethanol and 10mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0136] (4) Add 35g of bifunctional structure directing agent polyethylene glycol-distearate phosphatidylethanolamine to solution D and perform hydrothermal treatment at 165℃ for 5h. After hydrothermal treatment, cool to 25℃ to obtain solution E. Place solution E in an oven at 180℃ and the solvent will evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain modified mesoporous alumina.
[0137] Table 1. Properties of the modified mesoporous alumina obtained in each example.
[0138]
[0139] Table 2. Composition and properties of the hydrogenation catalysts obtained in each example.
[0140]
[0141]
[0142] Note: *In the obtained catalyst, the proportion of Brønsted acid to the sum of Brønsted acid and Lewis acid is represented by A;
[0143] **In the obtained catalyst, the proportion (%) of mesopore volume with a pore size of 6.0–25.0 nm to the total pore volume is represented by B; the proportion (%) of macropore volume with a pore size of 50.0–300.0 nm to the total pore volume is represented by C.
[0144] ***The percentage (%) of the amount of medium-strength acid in the obtained modified mesoporous alumina is represented by D.
[0145] Evaluation test
[0146] Activity stability tests were conducted on Examples 1-6 and Comparative Examples 1-6 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 977.4 kg / m³. 3 (20℃), S content 2.28wt%, Ni and V contents 26.1μg / g and 60.7μg / g respectively, CCR content 12.8wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others are relative demetallization rates. Specific experimental conditions are shown in Table 3, and experimental results are shown in Tables 4 and 5.
[0147] Table 3 Experimental conditions
[0148] Reaction temperature, °C 390 Reaction pressure, MPa 15.7 Liquid hourly space velocity, h -1 ]] 1.0 Hydrogen / oil ratio, V / V 650
[0149] Table 4. Test results of the hydrogenation demetallization catalysts in each example.
[0150]
[0151] Table 5. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0152]
[0153]
[0154] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A modified mesoporous alumina, wherein, The modifying element used in the modified mesoporous alumina is titanium. In the modified mesoporous alumina, the amount of medium-strong acid accounts for 59% to 65% of the total acid content, preferably 62% to 65%.
2. The modified mesoporous alumina according to claim 1, characterized in that, The modified mesoporous alumina has a specific surface area of 300–500 m². 2 / g, preferably 320-380m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–20.0 nm, and a pore volume of 1.10–1.50 mL / g, preferably 1.26–1.40 mL / g.
3. The modified mesoporous alumina according to claim 1, characterized in that, In the modified mesoporous alumina, the molar ratio of titanium to aluminum is 0.2 to 0.
8.
4. A method for preparing the modified mesoporous alumina according to any one of claims 1-3, comprising the following steps: (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A; (2) Mix the template agent and alcohol to obtain solution B; (3) Mix solution A, solution B and the solution containing titanium source to obtain solution D; (4) Add a bifunctional structure directing agent to solution D, perform hydrothermal treatment, dry, and calcine to obtain modified mesoporous alumina.
5. The preparation method according to claim 4, characterized in that, In step (1), the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide; the acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid; and the alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol. And / or, in step (1), the temperature of the pre-hydrolysis is 20-60°C and the time of the pre-hydrolysis is 1-12h; And / or, in step (1), the ethanol / aluminum molar ratio is 10.0 to 80.0, preferably 15.0 to 50.0; And / or, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 2.0 to 6.
0.
6. The preparation method according to claim 4, characterized in that, In step (1), the aluminum source, acid and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. And / or, the ionic emulsifier is one or more of sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt; Preferably, the amount of ionic emulsifier added is related to the amount of precursor solution used in a ratio of 5 to 15 g / 100 mL.
7. The preparation method according to claim 4, characterized in that, In step (2), the template agent is at least one of P123, SDBS and AOT, preferably P123; And / or, the molar ratio of the sum of the aluminum source in step (1) and the titanium source in step (3) to the molar ratio of the template agent in step (2) is 50 to 90; And / or, in step (2), the molar ratio of alcohol to template agent is 300 to 1000; And / or, the molar ratio of the titanium source in step (3) to the aluminum source in step (1) is 0.2 to 0.
8.
8. The preparation method according to claim 4, characterized in that, In step (3), the titanium source-containing solution includes a titanium source, an acid, and an alcohol, wherein the alcohol is preferably ethanol, the acid is preferably nitric acid, and the titanium source is selected from at least one of titanium isopropoxide, tetrabutyl titanate, methyl titanate, and tetraethyl titanate. And / or, in the titanium source-containing solution, the volume ratio of alcohol to acid is 4 to 12; And / or, in the titanium-containing solution, the ratio of the mass of titanium to the sum of the volumes of acid and alcohol is 0.02 to 0.15 g / mL.
9. The preparation method according to claim 4, characterized in that, In step (4), the bifunctional directing agent is polyethylene glycol-distearatephosphatidylethanolamine; Preferably, the molar ratio of the bifunctional structure directing agent to the sum of the bifunctional structure directing agent and the aluminum source in solution A is 0.05 to 0.
25.
10. The preparation method according to claim 4, characterized in that, In step (4), the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 165-245℃, and time 3-12h, preferably 4-8h; And / or, in step (4), the calcination temperature is 500-650°C and the calcination time is 3-8h.
11. A hydrogenation catalyst comprising a composite support containing a first active metal and a second active metal, wherein the composite support containing the first active metal comprises modified mesoporous alumina as described in any one of claims 1-3 or modified mesoporous alumina prepared by any one of claims 4-10, activated carbon, and the first active metal.
12. The catalyst according to claim 11, characterized in that, The first active metal is selected from at least one of Group VIB metals, preferably molybdenum; the second active metal is selected from at least one of Group VIII metals, preferably nickel; Preferably, in the composite carrier containing the first active metal, the mass ratio of modified mesoporous alumina to activated carbon is 2.5 to 6.0; Preferably, the catalyst contains, based on catalyst mass, 8.0% to 18.0% of Group VIB metal oxides, more preferably 10.0% to 15.0%, and 0.5% to 10% of Group VIII metal oxides, more preferably 1.0% to 6.0%.
13. The catalyst according to claim 11, characterized in that, In the catalyst, the mesopore volume with a pore size of 6.0 to 25.0 nm accounts for 20.0% to 48.0% of the total pore volume, preferably 41.5% to 48.0%, and the macropore volume with a pore size of 50.0 to 300.0 nm accounts for 20.0% to 35.0% of the total pore volume, preferably 24.5% to 35.0%. And / or, in the catalyst, the molar ratio of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and L-acid is 0.310 to 0.390, preferably 0.350 to 0.
388.
14. A method for preparing the catalyst according to any one of claims 11-13, comprising the following steps: (I) Modified mesoporous alumina, activated carbon, a first active metal source and molding aid are mixed and shaped, dried and calcined to obtain a composite carrier containing the first active metal. (II) The second active metal is loaded onto the composite support obtained in step (I), dried, and calcined to obtain the catalyst.
15. The preparation method according to claim 14, characterized in that, In step (I), the activated carbon is a high-temperature activated carbon with a minimum heat resistance temperature of not less than 700°C, preferably 700-800°C; And / or, the activated carbon has a pore volume of 1.0 to 1.8 mL / g, and the pore volume of pores with a diameter of 50.0 to 300.0 nm accounts for 15% to 40% of the total pore volume.
16. The preparation method according to claim 14, characterized in that, In step (I), the molding aid is one or more of guar gum powder and methylcellulose; Preferably, the molding aid is added at a mass of 1.0% to 8.0% of the total mass of the modified mesoporous alumina and activated carbon.
17. The preparation method according to claim 14, characterized in that, In step (I), the first active metal is one or more of the group VIB metals, preferably molybdenum; Preferably, the mass of the first active metal, calculated as oxide, is 10% to 20% of the total mass of mesoporous alumina and activated carbon.
18. The preparation method according to claim 14, characterized in that, In step (I), the calcination temperature is 500–650°C, and the calcination time is 3–8 hours. And / or, in step (II), the calcination temperature is 500-650°C and the calcination time is 3-8 hours.
19. The use of any catalyst according to claims 11-13 or any catalyst prepared by any method according to claims 14-18 in the hydrodemetallization of residue oil.
Citation Information
Patent Citations
Precious-metal-supported ordered mesoporous alumina material, and synthetic method and application thereof
CN104923215A
